Penegakan Hukum Terhadap Tindak Pidana Pencemaran Nama Baik di Muka Umum Berdasarkan Undang-Undang Nomor 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik di Polda Riau - Raja Desril; Salsabila Rabbani; Ali Ismail Shaleh (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2023)
In this era of globalization, with the increase in social media, there are also more defamation on social media. In order not to commit a crime in the name of the law. The purpose of this study was to determine law enforcement against criminal acts of crime both in public based on Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions at the Riau Police and to determine the inhibiting factors in law enforcement. criminal defamation in the Riau Police. The results of the study after conducting structured interviews with investigators of the Riau Regional Police Sub-Directorate 5 that in law enforcement the criminal act of defamation uses restorative justice to create justice. This restorative justice is carried out without coercion by any party on the condition that the reported party must provide material compensation due to the actions that have been committed. Restorative justice. One of the inhibiting factors in law enforcement of this crime is good for facilities and infrastructure. Because in the process of investigation, cyber investigations have difficulty because there are some devices that cannot be traced. This can cause harm to the victim